Peculiarities of Bacilli Ontogenesis During Cycle from a Spore to a Vegetative Cell - Voitsekhovsky, V.G.; Avdeeva, L.V.; Balko, O.B.; Balko, O.I.; Войцеховський, В.Г.; Авдєєва, Л.В.; Балко, О.Б.; Балко, О.І. (PH "Akademperiodyka" of the NAS of Ukraine, 2024)
In the review, on the example of aerobic spore-forming bacteria, the problems of the development and ontogenesis of the bacterial cell are considered along with the possibilities of influencing the course of these processes. The characteristics of the main concepts "growth", "differentiation", and "development" as independent processes with their dynamic interrelation are presented. Attention is focused on the analysis of literature data on the peculiarities of vegetative cell development, starting from a spore in a dormant state and finishing with vegetative form formation. In particular, the mechanisms that maintain the spore dormant state and subsequent processes of activation, initiation, outgrowth, and vegetative cell formation are described. There are emphasized certain problems with research on the ontogenesis of bacterial cells due to the deficiency of appropriate methods, as well as the lack of a single opinion regarding individual stages of the development and vegetative form formation. It was concluded that the study of individual stages of the development of prokaryotes, which differ in spore-forming and non-spore-forming microorganisms, is still relevant. Knowledge of these processes will help scientists to develop mechanisms of influence on the ontogenesis of microorganisms.